(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
There is need to solve the prominent issues of carbon monoxide hazards by promptly capturing it at the source. This paper presents the modelling and optimization analysis of the capture experimental results generated with independent use ofMonoethanolamine solution as sorbents for Post-combustion capture of CO from exhaust of Yamaha EF1000. The Yamaha EF1000 was appropriately connected to a laboratory scale glass absorber column for counter current flow of the flue gas with the sorbent. Modelling and optimization of the process were carried out using Design Expert version 10, with concentration of sorbents, process time and sorbent flow rate as the process variables. From the results obtained, quadratic models were obtained as the best model for the capture for the sorbent, with CO of the exit flue gas as response. Optimum response value of 4.139% at the respective factors of 20.044g/L, 5.666mins and 223.848cm3/min for sorbent concentration, process time and sorbent flow rates, were obtained. The strong correlation of the statistical modelling and response surface methodology with the experimental outcome made it evident that the variability observed in the experimental data can be relied upon in the design of prototype equipment which will serve for the pilot performance of such capture process.